A Pilot Study on Early-Onset Schizophrenia Reveals the Implication of Wnt, Cadherin and Cholecystokinin Receptor Signaling in Its Pathophysiology - Drozd, Malgorzata Marta; Capovilla, Maria; Previderé, Carlo; Grossi, Mauro; Askenazy, Florence; Bardoni, Barbara; Fernandez, Arnaud (Frontiers in Genetics, 2021)
Early-Onset Schizophrenia (EOS) is a very rare mental disorder that is a form of schizophrenia occurring before the age of 18. EOS is a brain disease marked by an early onset of positive and negative symptoms of psychosis that impact development and cognitive functioning. Clinical manifestations commonly include premorbid features of Autism Spectrum Disorder (ASD), attention deficits, Intellectual Disability (ID), neurodevelopmental delay, and behavioral disturbances. After the onset of psychotic symptoms, other neuropsychiatric comorbidities are also common, including obsessive-compulsive disorder, major depressive disorder, expressive and receptive language disorders, auditory processing, and executive functioning deficits. With the purpose to better gain insight into the genetic bases of this disorder, we developed a pilot project performing whole exome sequencing of nine trios affected by EOS, ASD, and mild ID. We carried out gene prioritization by combining multiple bioinformatic tools allowing us to identify the main pathways that could underpin the neurodevelopmental phenotypes of these patients. We identified the presence of variants in genes belonging to the Wnt, cadherin and cholecystokinin receptor signaling pathways.